PELAKSANAAN STRATEGI PENGEMBANGAN PENDIDIKAN DI POLITEKNIK KAMPAR - ", Aryadi; Sahuri, Chalid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Kampar Polytechnic developments in the journey was not free to do with the struggle Kampar District Government to develop the quality of human resources in the region. Then Kampar District Government Polytechnic entrust fully operational management of the Foundation Kampar Kampar Building (YKM), which was established by the Government before the fall of Kampar Kampar Politenik operasioan permission. This study was to determine the implementation strategy for the development of education conducted in Kampar Polytechnic, and to determine the factors that influence the development of education in the Polytechnic strategy Kampar.The location of this study is on the higher education institutions, namely the Polytechnic Kampar Kampar district. Informants in the study, namely: Employee Polytechnic Kampar, lecturers, students and community Kampar. Data analysis method used in this research is descriptive qualitative method of analysis using the SWOT analysis.Based on the research and the analysis that has been conducted on this study , it could take several conclusions Polytechnic education development strategy analysis Kampar Once known strengths , weaknesses / constraints , opportunities , and challenges / threats as mentioned above , the following described various efforts in overcome , namely : Expanding access and improving the quality of education and student affairs , Improving the quality of research and community service , resource capacity increase , Increased well-being , increased capacity of resources , strengthening management system , Improved welfare , well-being and strengthening Improved management systems . Factors affecting the development of educational strategies Polteknik Kampar in this study are : the National Environmental , Regional and International . Academic environment , institutional capacity and performance , financial resources and human resources swot analysis is based has not been fully utilized .Keywords: Strategy, Development Education, Polytechnic Kampar, SWOT